PENGARUH EKONOMI DIGITAL TERHADAP POLA KONSUMSI DAN INVESTASI MASYARAKAT DI WILAYAH KABUPATEN PONOROGO - Absor, Moh Ulil (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
This research aims to analyze the influence of the digital economy on consumption patterns and investment behavior in Ponorogo Regency. The study was conducted with a mixed-methods approach, combining quantitative data collection through surveys with qualitative insights from interviews and secondary sources. The results show that the adoption of digital payment systems such as QRIS and mobile wallets has significantly increased, reflecting a shift in consumer behavior toward more practical and efficient transactions. Moreover, digital platforms have encouraged investment diversification, with younger generations showing interest in online investment instruments such as mutual funds, stocks, and even cryptocurrencies, while older groups still prefer conventional savings and gold. These findings highlight that the digital economy has reshaped local economic behavior, creating both opportunities and challenges in improving financial literacy, inclusivity, and regional policy support. Keywords: Digital Economy, Consumption Patterns, Investment, Ponorogo